Case of Accidental Trauma Resulting in Condylar Fractures in 3-Month-Old - Maggie M. Mouzourakis; Sarah S. Seo; Resmiye Oral (Case Reports in Dentistry)
While mandibular fractures represent the most common craniofacial injury in the pediatric population, craniofacial fractures in infants are rare. Diagnosis is challenging with nonspecific presenting symptoms and often limited radiographic imaging. We report a case of nondisplaced mandibular condylar head fractures in a 3-month-old patient as a result of a fall with impact onto the chin, with associated sublingual hematoma (Coleman’s sign). Although the initially observed sole finding of sublingual hematoma raised concern for child physical abuse, detailed history, oral exam, and multidisciplinary review of radiologic records by pediatrics, otolaryngology, and child protection teams established the accidental trauma diagnosis. The patient was managed conservatively with normal resumption of feeding. Detailed history and multidisciplinary approach to the management of pediatric facial trauma are important in establishing diagnoses and management.